Participatory Action Research (PAR) Model for Developing A Tourism Village in Indonesia - Vina Salviana Darvina Soedarwo; Iqbal Ramadhani Fuadiputra; Mohammad Reevany Bustami; Gautam Kumar Jha (Universitas Muhammadiyah Malang, 2022)
The Participatory Action Research (PAR) Model is not only referred to as a research method but is also referred to as an approach to community empowerment and development, including community-based tourism development. This paper describes the stages of empowerment and development of a tourist village in Indonesia using the Participatory Action Research (PAR) approach consisting of observing, mapping, reviewing, making program diagram maps, and re-planning the development of tourist villages. The data obtained through the PAR approach were analyzed using the Nvivo 12 Plus Software. This paper reveals that Ngadas Village has tourism potential, including nature tourism and socio-cultural tourism. The tourism potential of Ngadas Village has not been managed and developed properly due to the limitations of village facilities and infrastructure that support the presence of Ngadas Village as a tourist village. The participatory integrative model is a model that can be implemented to develop Ngadas Village as an agriculture-based tourism village. Through this model, stakeholders, especially the village government, local government, universities, and local communities, can synergize and play a role according to their respective abilities, which are directed to realize the same goal, namely to build Ngadas Village as a tourist village as a source of opinion that supports community welfare. The findings of this study contribute to the development of local tourism in developing countries, especially in Indonesia.